Restoration of Spermatogenesis Using a New Combined Herbal Formula of Epimedium koreanum Nakai and Angelica gigas Nakai in an Luteinizing Hormone-Releasing Hormone Agonist-Induced Rat Model of Male Infertility - Hyun Jun Park (The World Journal of Men's Health, 2017)
Purpose: We investigated the protective effect of a mixture of 2 herbal extracts, KH-465, which consisted of Epimedium koreanum Nakai and Angelica gigas Nakai, on spermatogenesis in a luteinizing hormone-releasing hormone (LHRH) agonist-induced rat model of male infertility. Materials and Methods: Seventy-five 12-week-old male Sprague-Dawley rats were randomly divided into 5 groups, containing 15 rats each: a normal control group that received no treatment and 4 experimental groups (I, II, III, and IV) in which an LHRH agonist was administered for 4 weeks to induce spermatogenic failure. Group I received distilled water, and groups II, III, and IV received 200 mg/kg/day of KH-465, 400 mg/kg/day KH-465, and depo-testosterone for 4 weeks, respectively. Weight changes of the testis and epididymis, sperm count motility, and levels of testosterone (T), free T, follicle-stimulating hormone (FSH), luteinizing hormone (LH), superoxide dismutase (SOD), and 8-hydroxy-2’-deoxyguanosine (8-OHdG) were estimated. Results: Body, testis, and epididymis weight showed no significant differences among the control and experimental groups. Treatment with KH-465 increased the sperm count and motility. Serum hormone levels of T, free T, and FSH were not significantly different in the experimental groups, while the LH level was higher than in the LHRH agonist-induced control group, but not to a significant extent. Levels of SOD were higher and 8-OHdG were lower in the groups that received KH-465 than in the LHRH agonist-induced control group. Conclusions: Our results suggest that KH-465 increased sperm production via reducing oxidative stress and had a positive effect in a male infertility model.